Serial measurements of cortisol, creatine kinase, and TNF-a levels in elite basketball athletes during a training season - Tokatlidou, C.; Xirouchaki, C. E.; Kostopoulos, N.; Armeni, E. (Journal of Physical Education and Sport, 2021)
Objectives: The aim of this study was to explore the impact of different training interventions on cortisol and inflammatory cytokines in elite athletes. Materials and Methods: The current study consisted of male, healthy, elite, and professional basketball athletes aged 18-34 years old from two elite teams from Greece and Turkey. The current experimental procedure involved measurements of serum cortisol, tumor necrosis factor A (TNF- a), and creatine kinase (CK) levels as well as lymphocytes and neutrophils. The current study consisted of three different blood sample collection time points: before initiation, mid-season, and at the end of the training season. Statistical analysis was carried out using GraphPad Prism 9.2. Two-way Analyses of Variance (ANOVA) with repeated measures were performed for all the parameters. The P value was set at <0.05. Results: The Turkish elite athletes showed a 3.857-fold increase in TNFa in all measurements as well as 58% and 34% increases for the second and third measurements of cortisol compared to the Greek athletes. There was no statistically significant difference between the groups regarding serum CK, lymphocytes, and neutrophils. In addition, there was a trend of an increase in serum CK. However, it did not reach statistical significance. Conclusion: The current study shed light on the impact of different training regiments on cortisol and inflammatory cytokines. It was clearly highlighted how small training changes between countries can influence several biochemical markers. Our results highlight the crucial role of training design for cortisol and TNF-a levels in elite athletes during an entire training season.